Financial Performance Dynamics and Profitability Drivers in Retail Firms: A Panel Data Analysis - Agnes Fanny Laurent; Rilla Gantino (International Journal of Business, Management and Economics, 2026)
This study analyses the effect of accounts receivable turnover, asset growth, liquidity, leverage, and company size on profitability in retail sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2024. Of the 31 companies, 18 were selected as samples using purposive sampling. The analysis used panel data regression with the selected model being the common effect model. The results showed that accounts receivable turnover and company size had a significant positive effect on profitability, indicating that efficient accounts receivable management and greater company capacity could increase profits. Conversely, leverage has a significant negative effect, suggesting that excessive debt use reduces financial performance. Meanwhile, asset growth and liquidity have no effect on profitability. Managerially, these results imply the importance of optimizing accounts receivable management, controlling debt levels, and utilizing asset capacity to improve the efficiency and financial performance of retail companies.